Circular RNA in cardiovascular disease - Altesha, M‐Ashraf; Ni, Tiffany; Khan, Afaan; Liu, Kexiang; Zheng, Xiufen (Journal of cellular physiology, 2019)
Circular RNA (circRNA) are endogenous transcripts that display differential expression across species, developmental stages, and pathologies. Their lack of free ends confers increased stability when compared with linear transcripts, making them ideal candidates for future diagnostic biomarkers and therapeutic interventions. Increasing evidence has implicated circRNA in the pathogenesis of multiple cardiovascular diseases. In this paper, we summarize current understanding of circRNA biogenesis, properties, expression profiles, detection methods, functions, and their implication in cardiac pathologies including/ischemia reperfusion injury, myocardial infarction, cardiac senescence, cardiac fibrosis, cardiomyopathy, cardiac hypertrophy and heart failure, atherosclerosis, coronary artery disease, and aneurysm. Increasing evidence has implicated circular RNA (circRNA) in the pathogenesis of multiple cardiovascular diseases.This review provides scientists and clinicians with a brief summary of the ever‐growing world of circRNAs and their role in cardiac diseases specifically.